Roy's Adaptation Model in Reducing Academic Anxiety in Midwifery Students facing Midwifery Clinical Practice - Sari, Kurnia Indriyanti Purnamasari; Anggraeni, Widya; Idayanti, Titiek (Universitas Islam Lamongan, 2024)
Roy's adaptation model is designed to form an interrelated cycle consisting of input (stimulus), control process (coping mechanism), and output (response or behavior). The purpose of this study was to reduce academic anxiety in nursing students in facing midwifery clinical practice using Roy's model. The research design used a quasi experiment with a population of undergraduate nursing students with a sample size of 100 students. This study analyzed data using the T-test. From the demographic results, it was found that out of 100 respondents aged 20 years as many as 28 (28%), 58 (58%) men, 88 (54.2%) women. The results of data analysis using Shapiro Wilk obtained a probability value of 0.710> 0.05 so it can be concluded that the data is normally distributed. The mean ± SD value of the Academic Anxiety variable before the application of the Roy Adaptation Model is 43.99 ± 5. The mean ± SD value of the Academic Anxiety variable after the application of the Roy Adaptation Model is 192, while after the application of the Roy Adaptation Model is 45.59 ± 5.888. The results of the Paired Sample Statistics T-Test test obtained a value of 4.222 and a p value = 0.001 <0.05, thus the alternative hypothesis is accepted. For future researchers, it is expected to use stronger experimental designs such as randomized controlled experiments, conduct long-term measurements, analyze more complex data, include additional variables such as moderation or mediation and develop academic anxiety instruments.